Is fish bone subfossil a good archive of heavy metal pollution on Nandao Island, South China Sea?. (June 2019) - Wang, Xueying; Sun, Jing; Wu, Libin; Xu, Liqiang; Zhou, Yongli; Rao, Zixuan; Jin, Jing; Liu, Xiaodong
Abstract: To examine whether historical fish bones can record the magnitude of heavy metal pollution, we analyzed up to 700 years old fish bone remains extracted from an ornithogenic sediment profile on Nandao Island, South China Sea. Bulk sediments and subfossil fish bones were analyzed for elemental and mineralogical composition, as well as stable carbon and nitrogen isotopes. The results showed that pre-1850 CE fish bones experienced significant diagenesis, and could not be used to reconstruct historical record of heavy metal pollution. Fish bone diagenesis was mainly attributed to the erosion from guano in sediment profile. In contrast, the fish bones from in post-1850 CE time were well preserved and could provide useful information on historical pollution loads over the past 160 years. Since 1850 CE, relatively high concentrations of heavy metals from anthropogenic sources, especially Zn, were recorded in fish bone subfossils on Nandao Island, South China Sea. Graphical abstract: Unlabelled Image Highlights: FT-IR analysis indicated that fish bones before 1850 CE were poorly preserved. Diagenesis in fish bones possibly led to increase in Cu and Hg concentration. Diagenesis was affected by the erosion of guano in the ornithogenic sediments. Anthropogenic pollution especially Zn was detected in fish bones since 1850 CE.